Food Chain Transport of Nanoparticles Affects Behaviour and Fat Metabolism in Fish - Cedervall, Tommy; Hansson, Lars-Anders; Lard, Mercy; Frohm, Birgitta; Linse, Sara (PLOS ONE, 2012)
Nano-sized (10−9–10−7 m) particles offer many technical and biomedical advances over the bulk material. The use of nanoparticles in cosmetics, detergents, food and other commercial products is rapidly increasing despite little knowledge of their effect on organism metabolism. We show here that commercially manufactured polystyrene nanoparticles, transported through an aquatic food chain from algae, through zooplankton to fish, affect lipid metabolism and behaviour of the top consumer. At least three independent metabolic parameters differed between control and test fish: the weight loss, the triglycerides∶cholesterol ratio in blood serum, and the distribution of cholesterol between muscle and liver. Moreover, we demonstrate that nanoparticles bind to apolipoprotein A-I in fish serum in-vitro, thereby restraining them from properly utilising their fat reserves if absorbed through ingestion. In addition to the metabolic effects, we show that consumption of nanoparticle-containing zooplankton affects the feeding behaviour of the fish. The time it took the fish to consume 95% of the food presented to them was more than doubled for nanoparticle-exposed compared to control fish. Since many nano-sized products will, through the sewage system, end up in freshwater and marine habitats, our study provides a potential bioassay for testing new nano-sized material before manufacturing. In conclusion, our study shows that from knowledge of the molecular composition of the protein corona around nanoparticles it is possible to make a testable molecular hypothesis and bioassay of the potential biological risks of a defined nanoparticle at the organism and ecosystem level.